2015
DOI: 10.1111/eos.12246
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of adhesive penetration and resin bond strength to dentin using non‐thermal atmospheric pressure plasma

Abstract: Non-thermal atmospheric pressure plasmas (NT-APPs) have been shown to improve the bond strength of resin composites to demineralized dentin surfaces. Based on a wet-bonding philosophy, it is believed that a rewetting procedure is necessary after treatment with NT-APP because of its air-drying effect. This study investigated the effect of 'plasma-drying' on the bond strength of an etch-and-rinse adhesive to dentin by comparison with the wet-bonding technique. Dentin surfaces of human third molars were acid-etch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
36
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 35 publications
3
36
1
2
Order By: Relevance
“…However, the cohesive failure modes also increased after aging, corroborating the findings of the present study for the direct water exposure storage protocol. Previous studies have reported that NTAP treatment of dentin before application of etch‐and‐rinse adhesive increased the μ TBS , supporting the findings of the present investigation for the simulated pulpal pressure‐aging protocol.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…However, the cohesive failure modes also increased after aging, corroborating the findings of the present study for the direct water exposure storage protocol. Previous studies have reported that NTAP treatment of dentin before application of etch‐and‐rinse adhesive increased the μ TBS , supporting the findings of the present investigation for the simulated pulpal pressure‐aging protocol.…”
Section: Discussionsupporting
confidence: 91%
“…F). Previous reports are in agreement with these findings and the fourth null hypothesis might be rejected as NTAP treatment produced differences in interfacial regions, as analyzed by scanning electron microscopy. If a larger area of dentin matrix, exposed by the use of etch‐and‐rinse adhesives, induces higher enzymatic activity, it would be expected that the groups presenting larger numbers of dentin tubules filled with thicker resin tags would also present higher collagenolytic/gelatinolytic activity because the acidic monomers would be in more intimate contact with a larger area of the collagen fibril meshwork.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations